Remote data service installation on a grid-enabled Java platform - Blanco, E.; Cardinale, Y.; Figueira, C.; Hernandez, E.; Rivas, R.; Rukoz, M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
We define a framework for remote service installation, called SIMG (service installation metaservice on grids). Its main goal is to allow grid users to define and safely install their own data filters on remote data servers. Once installed, these filters may be used like the predefined services and may be available for a broader community of users. SIMG is implemented in SUMA/G, a Globus-enabled platform for remote execution of Java bytecode. We also present our experiences using SIMG for defining and remotely installing two complementary services in a content-based image retrieval system.